Asymptomatic Diagnosis of Huanglongbing Disease Using Metalloporphyrin Functionalized Single-Walled Carbon Nanotubes Sensor Arrays - Wang, Hui; Ramnani, Pankaj; Pham, Tung; Villarreal, Claudia Chaves; Yu, Xuejun; Liu, Gang; Mulchandani, Ashok (Frontiers in Chemistry, 2020)
Porphyrin with or without metal ions (MPs) owning to a lot of special physicochemical properties, have explored and applied in optical and electrochemical sensor fields. Four nitrogen atoms in the cen-ter of MPs make porphyrins chelate with almost metal ions, which change the binding ability of MPs with gas molecules via non-specific binding. In this article, we report a hybrid chemiresistor sensor ar-ray based on single-walled carbon nanotubes (SWNTs) noncovalently functionalized with six different MPs using the solvent casting technique. The characteristics of MPs-SWNTs were investigated though various optical and electro-chemical methods, including UV spectroscopy, Raman, atomic force micro-scope, current-voltage (I-V) and field-effect transistor (FET) measurement. The proposed sensor arrays were employed to monitor the four VOCs (tetradecene, linalool, phenylacetaldehyde and ethylhexanol) emitted by citrus trees infected with Huanglongbing (HLB), of which the contents changed dramatical-ly at the asymptomatic stage. The sensitivity to VOCs could change significantly that overcame the limits of SWNTs-based sensor. For qualitative and quantitative analysis of four VOCs, the data collect-ed by the sensor arrays was processed using different regression models containing partial least squares (PLS) and artificial neural network (ANN), which further offered a diagnostic basis for Huanglongbing disease at the asymptomatic stage.